2021
DOI: 10.1039/d0fo02890h
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects ofDendrobium officinaleon metabolic hypertensive rats by triggering the enteric-origin SCFA-GPCR43/41 pathway

Abstract: Given the increasing global trend toward unhealthy lifestyles and dietary decisions, such as “over-eating alcohol, and high sugar and fat diets” (ACHSFDs), it is no surprise that metabolic hypertension (MH)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…When vascular injury leads to endothelial dysfunction, NO synthesis decreases and ET-1 secretion increases, and this contributes to hypertension (Monica ET al., 2016;Wong et al, 2013). Our team previously found vascular endothelial injury in MH rats, and the expression of eNOS protein in the vessel and the NO level in the serum were significantly decreased (Li et al, 2021). Here, the plasma levels of eNOS and NO in MH rats were decreased, and the ET-1 level was increased, which was consistent with the previous results.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…When vascular injury leads to endothelial dysfunction, NO synthesis decreases and ET-1 secretion increases, and this contributes to hypertension (Monica ET al., 2016;Wong et al, 2013). Our team previously found vascular endothelial injury in MH rats, and the expression of eNOS protein in the vessel and the NO level in the serum were significantly decreased (Li et al, 2021). Here, the plasma levels of eNOS and NO in MH rats were decreased, and the ET-1 level was increased, which was consistent with the previous results.…”
Section: Discussionsupporting
confidence: 90%
“…Zhu et al suggested that an unhealthy diet is the initial culprit (Zhu et al, 2013). Thus, we established an MH model by induction with ACHSFD, which appears to simulate the unhealthy diets in many humans (Chen et al, 2015;Li et al, 2021). We found that several phenomena in the MH rats were similar to those in human MH patients, including high blood pressure and increasing of serum lipid levels and markers of liver damage.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations